2014
DOI: 10.1002/anie.201309718
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of Metal Nanoparticles: A Route to Colloidal Plasmonic Copolymers

Abstract: The resemblance between colloidal and molecular polymerization reactions has been recognized as a powerful tool for the fundamental studies of polymerization reactions, as well as a platform for the development of new nanoscale systems with desired properties. Future applications of colloidal polymers will require nanoparticle (NP) ensembles with a high degree of complexity that can be realized by hetero-assembly of NPs with different dimensions, shapes and compositions. In the present work, we have developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 49 publications
3
64
0
Order By: Relevance
“…[3a,e,f, 5, 6] Such ap rocess is analogous to polymerization in synthetic polymers but occurs at considerably larger length scales,s imilar to that observed in nanoparticle and Streptobacillus systems. [2,7] For example,P ochan et al prepared spherical micelles of poly(acrylic acid)-block-poly(methyl acrylate)-block-polystyrene in solution. [8] After introducing tetrahydrofuran (THF) into the solution in the presence of diamines,t he micelles underwent as phere-to-disk morphological transition, which allowed for preferential growth of the micelles in one dimension to form cylindrical nanostructures with alternating lamellae.T he success in creating such nanostructures by polymerizing pre-assemblies can be attributed to adirected stepwise self-assembly process that is facilitated by the anisotropy of the disk-like pre-assemblies and long-range electrostatic interactions between charged blocks with multivalent counterions.A lthough reports are available on the stepwise self-assembly process, [9] understanding the underlying principles still presents ac hallenge because of the complexity of these processes.Herein, we demonstrate astepwise self-assembly methodology for achieving one-dimensional growth of anisotropic pre-assemblies.O ur previous studies revealed that polypeptide-based graft copolymers bearing rigid a-helix blocks are able to self-assemble into distinct aggregates with unique structures,for example,anisotropic spindle-like micelles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[3a,e,f, 5, 6] Such ap rocess is analogous to polymerization in synthetic polymers but occurs at considerably larger length scales,s imilar to that observed in nanoparticle and Streptobacillus systems. [2,7] For example,P ochan et al prepared spherical micelles of poly(acrylic acid)-block-poly(methyl acrylate)-block-polystyrene in solution. [8] After introducing tetrahydrofuran (THF) into the solution in the presence of diamines,t he micelles underwent as phere-to-disk morphological transition, which allowed for preferential growth of the micelles in one dimension to form cylindrical nanostructures with alternating lamellae.T he success in creating such nanostructures by polymerizing pre-assemblies can be attributed to adirected stepwise self-assembly process that is facilitated by the anisotropy of the disk-like pre-assemblies and long-range electrostatic interactions between charged blocks with multivalent counterions.A lthough reports are available on the stepwise self-assembly process, [9] understanding the underlying principles still presents ac hallenge because of the complexity of these processes.Herein, we demonstrate astepwise self-assembly methodology for achieving one-dimensional growth of anisotropic pre-assemblies.O ur previous studies revealed that polypeptide-based graft copolymers bearing rigid a-helix blocks are able to self-assemble into distinct aggregates with unique structures,for example,anisotropic spindle-like micelles.…”
mentioning
confidence: 99%
“…Electron microscopy images also revealed that the length of the nanowires (associated with the number of repeat subunits) exhibited polydispersity.T oobtain insights into the structural details of the nanowires,wecalculated the number fraction f X of the nanowires with degree of polymerization (X). [7,11] This value was obtained by collecting SEM images with more than 400 micelles and then analyzing the images using Image-Pro Plus software (Supporting Information, Section 2). Here,t he degree of polymerization is defined as the number of spindles in ananowire.Asshown in Figure 1f, f X exhibited an exponential decay,and the number fraction of unreacted spindles (X = 1) was approximately 0.495.…”
mentioning
confidence: 99%
“…[1][2][3][4] To form am aterial with ad esired nanostructure,f undamental understanding has to be developed about the governing principles of the coassembly process.For example,the structure of linear chains assembled from different types of plasmonic NPs depends on the relationship between the rate of self-assembly of each individual component and the rate of coassembly. [5,6] Alternatively,o ne of the components can function as at emplate for the spatial organization of the second one. [7] Ap articularly interesting case is entropically mediated coassembly of NPs with different shapes,f or example,n anorods and nanospheres.T hese systems exhibit av ariety of structures,i ncluding macroscopic demixing of rods and spheres as well as microscopic and nanoscopic phase separation into layers of rods alternating with layers of spheres.…”
mentioning
confidence: 99%
“…Compared with individual AuNPs, the surface plasmon resonance peak of one dimensional (1-D) chains had a large red-shift from 530 to 625 nm, which possibly arose from the 1-D transverse plasmon coupling between AuNPs along chains 44. It further confirms the morphological transition of assemblies in solution at different pHs 45.…”
mentioning
confidence: 54%